2005
DOI: 10.1016/j.febslet.2005.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Apical cell adhesion molecule, trophinin, localizes to the nuclear envelope

Abstract: Trophinin mediates homophilic and apical cell adhesion between trophoblastic cells and endometrial epithelial cells, which is potentially the initial attachment step in human embryo implantation. Since trophinin is an atypical membrane protein without the signal sequence, it is possible that trophinin localizes to the cytoplasm. By treating trophinin-expressing trophoblastic cells with a series of detergents, we found significant levels of endogenous trophinin in the cytoplasm, particularly at the nuclear enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Previously we showed that endogenous magphinin‐α in human trophoblastic teratocarcinoma HT‐H cells is nuclear [Aoyama et al, 2005]. However, here magphinin‐α expressed in mouse NIH3T3 cells was cytoplasmic (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Previously we showed that endogenous magphinin‐α in human trophoblastic teratocarcinoma HT‐H cells is nuclear [Aoyama et al, 2005]. However, here magphinin‐α expressed in mouse NIH3T3 cells was cytoplasmic (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…To determine whether magphinin‐γ associates with the nuclear matrix, we undertook sequential extraction [He et al, 1990; Aoyama et al, 2005; Nakayama et al, 2006] (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations